2014
DOI: 10.5935/0103-507x.20140023
|View full text |Cite
|
Sign up to set email alerts
|

Adequacy of energy and protein balance of enteral nutrition in intensive care: what are the limiting factors?

Abstract: Objective To determine the factors that influence the adequacy of enteral nutritional therapy in an intensive care unit.Methods This prospective observational study was conducted in an intensive care unit between 2010 and 2012. Patients >18 years of age underwent exclusive enteral nutritional therapy for ≥72 hours. The energy and protein requirements were calculated according to the ICU protocols. The data regarding enteral nutrition, the causes of non-compliance, and the biochemical test results were collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
15

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 30 publications
0
11
0
15
Order By: Relevance
“…Entre os pacientes críticos, existe uma prevalência de desnutrição superior a 35% já na admissão em UTI. Isso também ocorre dentro do ambiente hospitalar, porém, na maioria das vezes, com maior intensidade devido à coexistência de fatores de risco 2 , variando entre 43 e 88% 3 .…”
Section: N T R O D U ç ã Ounclassified
See 2 more Smart Citations
“…Entre os pacientes críticos, existe uma prevalência de desnutrição superior a 35% já na admissão em UTI. Isso também ocorre dentro do ambiente hospitalar, porém, na maioria das vezes, com maior intensidade devido à coexistência de fatores de risco 2 , variando entre 43 e 88% 3 .…”
Section: N T R O D U ç ã Ounclassified
“…O paciente crítico é tipicamente associado a um estado de estresse catabólico e a uma resposta inflamatória sistêmica. Essa resposta está relacionada a complicações que levam ao aumento da morbidade infecciosa, da disfunção múltipla de órgãos, da hospitalização prolongada e da taxa de mortalidade [2][3][4][5] .…”
Section: N T R O D U ç ã Ounclassified
See 1 more Smart Citation
“…Oliveira Filho et al (30), encountered an average of > 80% of adequacy in infused ENT volume in oncological patients with NUTRIC > 6 and under MV, while Couto et al (33) showed values < 80% in politrauma patients and also under MV. In intensive care, to manage that patients receive a proper amount of prescribed ENT is a daily struggle, considering gastrointestinal intolerance such as abdominal distension, diarrhea and vomit or even pauses for procedures such as extubation or surgeries (30,34). Discrepancies observed between prescribed and infused volume had been reported by several authors as one of the main factors for hypoalimentation (5,18,19,29).…”
Section: Quality Indicators For Enteral and Parenteral Nutrition Thermentioning
confidence: 99%
“…The constant presence of the family and relatives during ICU stay might contribute to an increase in oral intake, mainly for elderly patients, because those are the ones who probably display a smaller percentage of oral intake recovery when compared to adult patients (34).…”
Section: Quality Indicators For Enteral and Parenteral Nutrition Thermentioning
confidence: 99%